PENGARUH PENAMBAHAN DAUN MINDI (Melia azedarach Linn) TERHADAP KUALITAS JAGUNG PIPILAN SELAMA PENYIMPANAN - Montesqrit Montesqrit; Harnentis Harnentis; Sri Yana (Udayana University, 2019)
This study aims to evaluate how the effect of the addition level of neem leaf flour (Melia azedarach Linn) on the quality of shelled corn during storage. The research material used was neem leaves, shelled corn, storage containers and analytical equipment. Neem leaves are given in the form of flour with a size of 60 mesh while corn used in shell corn with water content and aflatoxin content before storage are 20% and 110 ppb respectively. Shelled corn was used as much as 1 kg for each treatment and stored in modified woven bags for 4 weeks. The research method is an experimental method using a completely randomized design (CRD), with 4 treatments and 4 replications. The treatments were the percentage of neem leaf flour addition in shelled corn, the four treatments were treatment A (0% neem leaf flour), B (2.5% neem leaf flour), C (5% neem leaf flour), and D ( 7.5% neem leaf flour). Parameters measured were percentage of damaged seeds, percentage of moldy seeds, moisture content and aflatoxin content. The results of the study showed that the treatment had a highly significant effect (P<0.01) on% of damaged seeds, % of moldy seeds, and aflatoxin content on shelled corn during storage. The administration of neem leaf flour at 2.5% level was able to maintain the quality of shelled corn during storage, where the aflatoxin content could decrease from 110 ppb before storage to 34,25 ppb after being stored for 4 weeks. Keywords: neem (Melia azedarach Linn), shelled corn, storage, aflatoxin